Temporal dynamics of the hydropower water reservoirs of the Tocantins–Araguaia Basin, Brazil, based on remote sensing and hydrometeorological station datasets - Valadão, Larissa Vieira (2023)
The Tocantins–Araguaia Basin covers an extensive area of Brazilian territory and has a water reservoir system installed in a cascade that is very important for water storage and hydropower production. There is concern about the use of this resource because of the current tendency of surface water reduction in the reservoir systems. Sustainable management can help to guarantee the water supply and the hydropower supply. However, accurate data on the monitoring parameters are required. This study aims to analyze which factors most influence the changes in the areas of water reservoirs and, subsequently, the changes in the water availability. Trends, correlations, and principal component analyses (PCAs) were used to assess the association between the areas of water reservoirs and the liquid evaporation, discharge, precipitation, and land use and land cover (LULC) in the basin. We observed that the precipitation did not decrease significantly. On the other hand, changes in the LULC and the areas of reservoirs were highly correlated with each other. The PCA also showed a strong association between meteorological factors and the areas of reservoirs. In conclusion, this study showed that reductions in the areas of water reservoirs are mostly related to deforestation and reduced reservoir discharge rather than climate change. This paper provides a straightforward approach to monitoring reservoir changes based on the tendencies of some parameters that are strongly correlated with reservoir changes.